Annual air temperature variability and biotic interactions explain tundra shrub species abundance. (27th March 2021) - von Oppen, Jonathan; Normand, Signe; Bjorkman, Anne D.; Blach‐Overgaard, Anne; Assmann, Jakob J.; Forchhammer, Mads; Guéguen, Maya; Nabe‐Nielsen, Jacob
Abstract: Questions: Shrub vegetation has been expanding across much of the rapidly changing Arctic. Yet, there is still uncertainty about the underlying drivers of shrub community composition. Here, we use extensive vegetation surveys and a trait‐based approach to answer the following questions: which abiotic and biotic factors explain abundance of shrub species and functional groups in the Arctic tundra, and can we interpret these relationships using plant traits related to resource acquisition? Location: Nuup Kangerlua (Godthåbsfjord), western Greenland. Methods: We tested the power of nine climatic, topographic and biotic variables to explain the abundances of nine shrub species using a Bayesian hierarchical modelling framework. Results: We found highly variable responses among species and functional groups to both abiotic and biotic environmental variation. The overall most important abiotic explanatory variable was annual air temperature variability, which was highly correlated with winter minimum air temperature. Functional community composition and graminoid abundance were the most influential biotic factors. While we did not find systematic patterns between shrub abundances and abiotic variables with regard to resource acquisition traits, these traits did explain relationships between shrub abundances and biotic variables. Conclusions: Shrub abundance responses to abiotic variables rarely aligned with expectations based on plants' resource acquisition traits or functional groups. Our results, therefore, indicate that approaches exclusively based on resource acquisition traits might be limited in their ability to predict abundances of individual groups and species, particularly in response to complex abiotic environments. However, integrating community theory and functional trait concepts represents a promising pathway to better predict biotic interactions and ultimately responses of dominant shrub vegetation to rapid environmental changes across the arctic tundra biome. Abstract : We used a trait‐based approach to evaluate abiotic and biotic factors for the abundance of dominant shrub species. Annual air temperature variability and biotic interactions explained most variation in shrub abundances, but species' relationships with environmental variables were highly individualistic, rarely aligning with their functional traits. Our findings highlight potential challenges in predicting future dynamics of tundra vegetation. (Photo: Urs A. Treier).